2004
DOI: 10.15666/aeer/03035043
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics Study of Methylene Blue Dye Bioadsorption on Baggase

Abstract: A Ab bs st tr ra ac ct t. The adsorption potential of agricultural (sugarcane) by-product, the baggase was investigated in batch experiments with two different forms i.e., raw and chemically activated forms, for the removal of Methylene Blue dye, with different parameters like dye concentration, contact time, temperature and adsorbent dose. The removal is better and more effective with chemically activated baggase in comparison to the raw baggase. An average percent removal difference between the two adsorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 8 publications
1
66
0
4
Order By: Relevance
“…One part of both the adsorbents is treated with HCHO, and other part is treated with H 2 SO 4 . The purpose of pre-treatment of raw adsorbent with formaldehyde is to remove the colour of raw adsorbents, which can interfere with the dye studied in order to achieve maximum colour removal with accuracy, whereas the acid treatment of both the adsorbents is done due to significant performance recorded by acid-treated adsorbents in past (Garg et al 2003;Raghuvanshi et al 2004;Parvathi et al 2010). Adsorption isotherm and chemical kinetics are considered to find out the nature and mode of adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…One part of both the adsorbents is treated with HCHO, and other part is treated with H 2 SO 4 . The purpose of pre-treatment of raw adsorbent with formaldehyde is to remove the colour of raw adsorbents, which can interfere with the dye studied in order to achieve maximum colour removal with accuracy, whereas the acid treatment of both the adsorbents is done due to significant performance recorded by acid-treated adsorbents in past (Garg et al 2003;Raghuvanshi et al 2004;Parvathi et al 2010). Adsorption isotherm and chemical kinetics are considered to find out the nature and mode of adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…The polluted water is also harmful to animals and human beings as the dyes and their metabolites are highly toxic [6,7] and carcinogenic [8,9] in nature. The passivity of the dyes in the presence of heat, light, microbes, and even oxidizing agents makes the degradation of coloring material difficult [10]. This is attributed to the complex structure of the dyes.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that in the world several million tons of agricultural wastes are being disposed of every year. In India alone more than 400 million tons of agricultural residue is generated annually [41], and it is estimated that the production of coir pith in India is 0.5 million tons, and coir pith is disposed of as a waste and its accumulation around coir-processing centers is creating a menace [42]. And about 3.5 million tons of tea are consumed worldwide [17].…”
Section: Adsorbent Resourcesmentioning
confidence: 99%
“…In the last few years, the consumption of coffee has rapidly increased, especially by young people. According to a survey done by Sulyman (2016) [5], which included 25 cafes in the city of Tripoli, Libya, the average generation of coffee ground wastes by only the 25 cafes is estimated to be in the range of (36)(37)(38)(39)(40)(41)(42)(43)(44)(45) tons annually, and a big volume of this waste is still kept in big plastic bags for disposal by conventional methods, which are burned or dumped. It is also estimated that in one of these cafes, more than 100 cups of coffee are drunk within an hour, while in the city of Gdansk, Poland, at one café that was surveyed, more than 1,600 cups of coffee are consumed daily.…”
Section: Adsorbent Resourcesmentioning
confidence: 99%